Interactive, Constraint-based Layout of Engineering Diagrams - Dwyer, Tim; Marriott, Kim; Wybrow, Michael (Electronic Communications of the EASST, 2008)
Many engineering disciplines require visualisation of networks. Constrained graph layout is a powerful new approach to network layout that allows the user to impose a wide variety application-specific placement constraints—such as downwards pointing directed edges, alignment of nodes, cluster containment and non-overlapping nodes and clusters—on the layout. We have recently developed an efficient algorithm for topology-preserving constrained graph layout. This underpins two dynamic graph layout applications we have developed: a network diagram authoring tool, Dunnart, and a network diagram browser. In this paper we provide an overview of topology-preserving constrained graph layout and illustrate how Dunnart and the network diagram browser can be applied to engineering diagram authoring and visualisation.